A sialidase mutant displaying trans-sialidase activity - Paris, Gastón (2005)
Trypanosoma cruzi, the agent of Chagas disease, expresses a modified sialidase, the trans-sialidase, which transfers sialic acid from host glycoconjugates to β-galactose present in parasite mucins. Another American trypanosome, Trypanosoma rangeli, expresses a homologous protein that has sialidase activity but is devoid of transglycosidase activity. Based on the recently determined structures of T. rangeli sialidase (TrSA) and T. cruzi trans-sialidase (TcTS), we have now constructed mutants of TrSA with the aim of studing the relevant residues in transfer activity. Five mutations, Met96-Val, Ala98-Pro, Ser120-Tyr, Gly249-Tyr and Gln284-Pro, were enough to obtain a sialidase mutant (TrSA 5mut) with trans-sialidase activity; and a sixth mutation increased the activity to about 10% that of wild-type TcTS. The crystal structure of TrSA 5mut revealed the formation of a trans-sialidase-like binding site for the acceptor galactose, primarily defined by the phenol group of Tyr120 and the indole ring of Trp313, which adopts a new conformation, similar to that in TcTS, induced by the Gln284-Pro mutation. The transition state analogue 2,3-didehydro-2-deoxy-N-acetylneuraminic acid (DANA), which inhibits sialidases but is a poor inhibitor of trans-sialidase, was used to probe the active site conformation of mutant enzymes. The results show that the presence of a sugar acceptor binding-site, the fine-tuning of protein-substrate interactions and the flexibility of crucial active site residues are all important to achieve transglycosidase activity from the TrSA sialidase scaffold.